The dilemma of cystectomy in old-old and oldest-old patients. Issue 12 (December 2011) - Pycha, Armin; Comploj, Evi
Bladder cancer (BC) is a disease of the elderly, with a peak incidence at 85 years. If life expectancy continues to increase in such a way that it is, in 20 years nearly half of the population will be considered elderly. The incidence of BC will also dramatically increase in proportion to this and, subsequently, a cure is needed. Currently, only 4–11% of elderly individuals with muscle-invasive BC undergo radical extirpative surgery; a number that is evidently too low when we consider that the cancer-specific mortality rate is highest in the octo- and nona-genarian groups. Advanced age should not in itself be a reason for avoiding radical surgery. Comorbidity is much more important and incisive on complication and mortality rate than age alone. Nevertheless, a complication rate of 24–60% is a realistic expectation, as is a 90-day mortality rate of approximately 10%. Due to the restricted physiological reserve, there is little place for surgical mistakes. This review evaluates all aspects of radical cystectomy in the elderly and gives an overview of upcoming challenges.